Are Europe's Social Security Finances Compatible with EMU? - Kopits, George (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1997)
Pursuant to the Treaty of Maastricht, members of the European Union (EU) intend to participate in the Economic and Monetary Union (EMU), in part through convergence toward specified limits on the overall deficit and gross debt of general government. The paper argues that in several EU members, the financial imbalance of social security institutions may constitute an impediment to meeting these requirements. Given a constraint on further payroll tax increases, most countries will need to undertake major reform of public pension and health-care systems, to ensure adherence to the EMU fiscal criteria in the medium to long run.